2012
DOI: 10.1089/dna.2012.1798
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated TCRζ Enhances Interleukin-2 Production in T-Cells from Patients with CML

Abstract: T-cell immunodeficiency is a common feature in patients with chronic myeloid leukemia (CML), and deficiency in CD3 levels was detected in T cells from these patients, which may represent a characteristic that is related to a lower T cell activation. In this study, we explored the possibility that forced TCRζ gene expression may upreg-u-late T cell receptor (TCR) signaling activation and reverse interleukin-2 (IL-2) production in T cells from patients with CML. A recombinant eukaryotic vector expressing TCRζ wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…The TCRf chain is considered to be a limiting factor for the assembly and transport of the complex to the cell surface, which is crucial for receptor signaling functions as it provides 6 of 10 immunoreceptor tyrosinebased activation motifs (ITAMs) for the complex (Call and Wucherpfennig, 2005;Li, 2008;Zha et al, 2012a). TCRf chain tyrosine phosphorylation is the first step in the signal transduction cascade initiated after TCR/CD3 engagement followed by phosphorylation of the cellular substrate ZAP-70 (TCRf chain-associated protein kinase 70 kDa), a cytosolic protein.…”
Section: Introductionmentioning
confidence: 99%
“…The TCRf chain is considered to be a limiting factor for the assembly and transport of the complex to the cell surface, which is crucial for receptor signaling functions as it provides 6 of 10 immunoreceptor tyrosinebased activation motifs (ITAMs) for the complex (Call and Wucherpfennig, 2005;Li, 2008;Zha et al, 2012a). TCRf chain tyrosine phosphorylation is the first step in the signal transduction cascade initiated after TCR/CD3 engagement followed by phosphorylation of the cellular substrate ZAP-70 (TCRf chain-associated protein kinase 70 kDa), a cytosolic protein.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, enhancing CD3 expression may reactive the T cell activation functions and reverse the immunodeficiency in leukemia patients. Enhancement in TCRz (CD3z), which is crucial for TCR signaling functions, because it provides 6 of 10 immunoreceptor tyrosine-based activation motifs for the TCR-CD3 complex (Call and Wucherpfennig, 2005;Li, 2008;Zha et al, 2012a), was reported by different methods, including cytokine induction and TCRz transfer in T cells of CML patients (Chen et al, 2009;Zha et al, 2012b). A previous study showed that IL-2 could enhance the TCRf level, but it could not completely recover the TCRf level in T cells in CML patients (Chen et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…T cells from patients with leukemia are functionally impaired, and this is related to a decrease in the TCRz chain expression (Chen et al, 2000;Fischer et al, 2005;Li, 2008;Chen et al, 2011). Recently, we have reported significantly lower expression of TCRf in patients with AML and CML, and increasing TCRz expression by gene transfer enhances the activation and cytotoxicity of T cells from patients with CML (Chen et al, 2009;Zha et al, 2012aZha et al, , 2012b. However, there are few data characterizing TCRz upregulation and the T cell activation and proliferation induced by different methods such as gene transfer and cytokine induction in T cells from AML.…”
Section: Introductionmentioning
confidence: 99%
“…Cells were collected by centrifugation and resuspended at 2.5 · 10 6 cells for Molt-4 and Jurkat cells per 100 mL of the appropriate NucleofectorÔ kit solution (Amaxa Biosystems) (Huang et al, 2011;Chen et al, 2012;Zha et al, 2012). Malignant T cells were nucleofected with 3 mg of PPP2R5C-siRNAs or a control nonsilencing scrambled (SC) siRNA using the C-005 (Molt-4 cells) or X-001 ( Jurkat cells) program of the Nucleofection Device II (Amaxa Biosystems).…”
Section: Nucleofectionmentioning
confidence: 99%